2020
DOI: 10.3171/2020.4.spine191390
|View full text |Cite
|
Sign up to set email alerts
|

Flexible endoscope visualization to assist in the removal of a string of 10 schwannomas at the cauda equina: technical case report

Abstract: Bead-like schwannomas at the cauda equina are rare but benign intraspinal tumors. They can involve multiple nerve roots and spread within the spinal canal, and open resection would cause significant trauma. The authors have successfully applied a novel minimally invasive technique for the total removal of such schwannomas. A 68-year-old woman presented with a 1-month history of left waist and leg pain. MRI demonstrated multiple intraspinal lesions located from L1 to S1. The diagnosis was bead-like schw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Di et al similarly observed reductions in soft tissue injury, blood loss, incision length, postoperative pain, and hospitalization duration in patients who underwent the UHNV procedure ( 56 ). Besides, Ren et al reported that UHNV was an effective minimally invasive procedure that reduced the presence of residual tumors in treated patients ( 57 ). Overall, small bony fenestrations or enlarged interlaminar corridors offer a similar effect to tubular retractors, and using endoscopy with “tubular retractors” provides a better view than “tubular” microsurgery.…”
Section: Discussionmentioning
confidence: 99%
“…Di et al similarly observed reductions in soft tissue injury, blood loss, incision length, postoperative pain, and hospitalization duration in patients who underwent the UHNV procedure ( 56 ). Besides, Ren et al reported that UHNV was an effective minimally invasive procedure that reduced the presence of residual tumors in treated patients ( 57 ). Overall, small bony fenestrations or enlarged interlaminar corridors offer a similar effect to tubular retractors, and using endoscopy with “tubular retractors” provides a better view than “tubular” microsurgery.…”
Section: Discussionmentioning
confidence: 99%